THE RELATIONSHIP BETWEEN THE USE OF MICROSOFT TEAMS AND LEARNING MOTIVATION TO THE LEARNING EFFECTIVENESS OF STUDENTS IN S1 MANAGEMENT PROGRAM FACULTY OF ECONOMICS AND BUSINESS INDONESIAN CHRISTIAN UNIVERSITY DURING THE COVID-19 PANDEMIC - Verawaty Rosauli Manurung; Suzanna Josephine Tobing; Lenny Panggabean (Fundamental Management Journal, 2023)
This study aims to find out and prove whether the use of Microsoft Teams and learning motivation have a relationship with learning effectiveness. Using a quantitative descriptive approach, this study collected data from students of Management Study Program, Faculty of Economics and Business, Indonesian Christian University through a questionnaire. The population in this study were students of Management Study Program, Faculty of Economics and Business, Indonesian Christian University. The sample used was 75 respondents. Sampling was carried out using the Likert scale technique. Data analysis used correlation analysis techniques, Rank Spearmen correlation analysis. The test results using SPSS show that there is a significant relationship between the use of Microsoft Teams and learning motivation on learning effectiveness. The test results show that (1) There is a significant relationship between the use of Microsoft Teams and the learning effectiveness of students of Management Study Program, FEB, Indonesian Christian University, with the Rank Spearmen correlation coefficient (0.587), which indicates a fairly strong correlation. (2) There is a significant relationship between learning motivation and learning effectiveness of S1 Management study program students at the FEB Indonesian Christian University with the Rank Spearmen correlation coefficient (0.594) which shows a fairly strong correlation. Keywords: Use of Microsoft Teams, Learning Motivation, and Learning Effectiveness.